Synthesis guided by multivariate analysis of computational descriptors and electrochemical evaluation of aniline-based Schiff bases as potential corrosion inhibitors in acidic media - Carlos Andrés Coy-Barrera; Lili Dahiana Becerra; Vicky Carolina Gonzalez; Diego Quiroga (Results in Surfaces and Interfaces, 2025)
Using the density functional theory (DFT), we analyzed the electronic properties of 42 Schiff bases, revealing key descriptors such as HOMO, LUMO and electronegativity, which correlate with their reactive behavior and adsorption. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) identified five clusters linked to different corrosion inhibition potentials. The most promising compounds exhibited high electron donation capabilities, increasing their potential adsorption on metallic surfaces of carbon steel. Compounds with electron removal groups (EWGs), such as 4-NO2Ph, showed reduced antioxidant activity by the effect of the nitro group on electron density, whereas bulky substituents such as 4-tBuOPh displayed a moderate antioxidant activity, this indicates that groups (EWgs) with antioxidant activity are related to the % of corrosion inhibition. Although they are different processes it is evident that the presence of such substituents, which are abundant in the literature, can be utilized as organic inhibitors. Subsequently, promising compounds, based on the theoretical and statistical study were evaluated in corrosion inhibition processes on carbon steel surfaces in an acid medium (HCl 1.0 M), by potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). Compounds containing EWGs, particularly halogens, exhibited high inhibition efficiency. Compound (E)-1-(4-chlorophenyl)-N-phenylmethanimine demonstrated excellent performance, with high charge transfer resistance and inhibition efficiency (95.54 %), suggesting effective protection against corrosion. In contrast, compound (E)-1-(4-nitrophenyl)-N-phenylmethanimine showed limited inhibition with low impedance and unstable protective films. Surface morphology analysis by scanning electron microscopy (SEM) revealed that coatings with compound (E)-1-(4-chlorophenyl)-N-phenylmethanimine had more uniform textures and better corrosion resistance, while compound (E)-1-compound(4-(tert-butoxy)phenyl)-N-phenylmethanimine exhibited moderate inhibition but more uniform surface characteristics. The evaluated molecules do not have prior information in this type of test. The results obtained also highlight the importance of electronic properties and surface microstructure in the effectiveness of Schiff base compounds as corrosion inhibitors, highlighting their potential for the development of multifunctional protective coatings.